Pembaharuan Mekanisme Eksekusi Putusan Peradilan Tata Usaha Negara Melalui Revitalisasi Khususnya Peran Kejaksaan - Josiano Leo Haliwela (Jurnal JURISTIC, 2025)
The implementation of the TUN Decision which has Permanent Legal Force (BHT) becomes a "toothless tiger" because it is not implemented by the losing party, in this case the "Defendant" (TUN Officials), resulting in the authority of the TUN Decision (TUN Judiciary) being lowered. In this regard, there are several factors that cause the implementation of decisions that have permanent legal force (BHT) cannot be executed/implemented, including: 1). The person who is the executor of the implementation of the TUN Decision which has Permanent Legal Force (BHT) is the Defendant himself, where the Defendant should be willing to implement the TUN Decision which has BHT. 2). The problem of dwangsom (forced money) which is only around Rp. 250,000,- up to Rp. 5,000,000,-., who should be charged to whom? 3). Lack of awareness of public officials as defendants in complying with legal regulations or complying with the judge's decision in order to create justice and legal harmony. 4). There is no special executorial institution or sanctioning institution whose function is to implement decisions, because the problem of non-compliance with PTUN decisions and/or determinations lies not only in unclear regulations or the absence of implementing rules regarding coercive measures, but also in which institution is supposed to ensure implementation of the decision. Another thing in criminal law is that the executor or institution that is authoritative for the implementation of judicial decisions for criminal cases is clear and firm, namely the Prosecutor's Office (in this case Jampidsus/Junior Attorney General for Special Crimes), while for civil cases, namely the Court Bailiff/Junior Attorney General for Civil Affairs. and State Administration (Jam Datun).